Investigating Male Presence at Antenatal and Choice of Place for Child Delivery in Ghana - Doegah, Phidelia Theresa (Frontiers in Public Health, 2019)
Male involvement in maternal health was introduced to improve and sustain maternal and child health in Ghana. The study utilised the 2014 Ghana Demographic and Health Survey data to investigate the relationship between male presence at antenatal and choice of place of child birth among 1,167 males, 15-59 years. Descriptive and analytical statistical techniques were applied to the data. The binary logistic regression shows no association between male presence at antenatal and place of delivery (IRR= 1.197; 95% CI= 0.808‒1.773). However, age (IRR= 2.647; 95% CI= 1.221‒5.736, IRR= 3.046; 95% CI= 1.345‒6.896, IRR= 3.513; 95% CI= 1.478‒8.345), level of education (IRR= 4.478; 95% CI= 1.412‒14.1990, religion (IRR= 0.473; 95% CI= 0.237‒0.946), ethnicity (IRR= 0.400; 95% CI= 0.182‒0.877, IRR=0.425; 95% CI 0.194‒0.935), marital status (IRR= 5.682; 95% CI= 2.093‒15.421, IRR= 5.669; 95% CI= 1.448‒22.198), place of residence (IRR= 7.272; 95% CI= 4.231‒12.499), and region of residence (IRR= 11.515; 95% CI= 2.785‒47.618) of males were found associated with health facility based delivery. Thus regarding policy to promote institutional delivery among women, these factors should be considered.